E-Report System to Help Monitor Student Academic Progress Using Forward Chaining for Grade Promotion According to Student Development Level - Ibnu Utomo Wahyu Mulyono; Novita Kurnia Ningrum; Zahrotul Umami; Karis Widyatmoko (Universitas Dian Nuswantoro and IndoCEISS, 2021)
The COVID-19 pandemic that has occurred in the world and Indonesia is one of the affected countries. To limit the rate of transmission of COVID-19, the Ministry of Education issued regulations relating to online schools. With this online school, both parents and teachers need media to be able to monitor students' academic progress as long as online schools are implemented. Therefore, we need a system that can assist teachers and parents in monitoring students' academic progress. In this study, an e-report was designed by incorporating the components of students' academic aspect and students' character aspect. This system is supported by a decision support system using forward chaining to determine the feasibility of a grade increase according to the level of development of the student. The output of this system is student grade reports, advice given to parents and grade promotion decisions based on academic and character aspect.